A sheet from the history of sculpture - Djabborov Dilshod Turdikulovich (Genius Publishing Group, 2022)
A sculpture is a three-dimensional, human-made object selected for special recognition as art. Every culture since the beginning of human existence has sculpted objects that have lasted hundreds or even thousands of years. Sculpture as a three dimensional object is different from other art in that it is also tactile and allows even the blind to experience it. As intelligence develops the human ability to use the materials of the external world develop.
Keywords: Sculpture; Human-Made; Culture; Realism